Introduction of sungai pinang village website, rambutan district, banyuasin district, selatan sumatra based on ict towards a digital smart village program - Ali Ibrahim; Mira Afrina; Yadi Utama; Ahmad Fali Oklilas (Peneliti Teknologi Teknik Indonesia, 2022)
Community service activities can be carried out according to the agreed agenda and schedule between the community service team and the team from the Sungai Pinang village head, in this case represented by the village head and the village secretary. From the results of the evaluation during the implementation of the activity, it was found that the enthusiasm of the participants was very high in accepting what was conveyed by the resource person. In addition, from the results of communication with the Sungai Pinang village team, it is hoped that there will be further training from the community service team for 2022. So that there will be a continuation of activities. The success rate for this activity is around 75%. Methods in community service activities, mentoring and counseling. The target of this activity is the village staff of more than 10 village staff and 20 representatives from the village community. Village representatives consist of youth organizations, RT, RW and the community.